Letters of a Sufi scholar : the correspondence of ʻAbd al-Ghanī al-Nābulusī (1641-1731) - Akkach, Samer. (Islamic History and Civilization, 2010)
As a leading Muslim thinker, 'Abd al-Ghanī al-Nābulusī of Damascus creatively engaged with the social, religious, and intellectual challenges that emerged during the early modern period in which he lived. Yet, at a time of high anti-mystical fervour, his Sufi-inspired views faced strong local antipathy. Through extensive correspondence, presented here for the first time, 'Abd al-Ghanī projected his ideas and teachings beyond the parochial boundaries of Damascus, and was thus able to assert his authority at a wider regional level. The letters he himself selected, compiled, and titled shed fresh lights on the religious and intellectual exchanges among scholars in the eastern Ottoman provinces, revealing a dynamic and rigorous image of Islam, one that is profoundly inspired by humility, tolerance, and love. http://tntypography.com/brill.html